Integrating Islamic Culture in English as A Foreign Language (Efl) Teaching: Importance and Implications - Kalayo Hasibuan; Fatma Insania Sakinah; Gusdiva Arieyanti; Kartika Meilisa (Lembaga Pengembangan Kinerja Dosen, 2025)
This article explores the integration of Islamic culture into English as a Foreign Language (EFL) teaching, emphasizing its importance and implications for Muslim students. It discusses the concepts of Islamic culture, the role of culture in language learning, and practical strategies for incorporating Islamic values into EFL curricula. The findings suggest that integrating Islamic culture not only enhances language acquisition but also strengthens students' identities and moral character.